2018
DOI: 10.1159/000489546
|View full text |Cite
|
Sign up to set email alerts
|

Resistin Regulates Fatty Acid Β Oxidation by Suppressing Expression of Peroxisome Proliferator Activator Receptor Gamma-Coactivator 1α (PGC-1α)

Abstract: Background/Aims: Abnormal fatty acid β oxidation has been associated with obesity and type 2 diabetes. Resistin is an adipokine that has been considered as a potential factor in obesity-mediated insulin resistance and type 2 diabetes. However, the effect of resistin on fatty acid β oxidation needs to be elucidated. Methods: We detected the effects of resistin on the expression of fatty acid oxidation (FAO) transcriptional regulatory genes, the fatty acid transport gene, and mitochondrial β-oxidation genes usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…This is consistent with Kim's report that DNA hypermethylation of a particular region of the adiponectin promoter suppressed adiponectin expression through epigenetic control mediated by a higher DNMT1 expression and, in turn, exacerbated metabolic complications in obesity [12]. However, the expression of resistin and its epigenetic modification are still in controversy [34][35][36][37][38][39][40][41][42][43][44][45][46]. Kim et al found that, in the DIO rats, the expression levels of different genes in adipose tissue including resistin were upregulated [45], whereas Nowacka-Woszuk reported reduction in the resistin expression in the DIO rats, and no correlation of DNA methylation with transcript levels were observed [46].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with Kim's report that DNA hypermethylation of a particular region of the adiponectin promoter suppressed adiponectin expression through epigenetic control mediated by a higher DNMT1 expression and, in turn, exacerbated metabolic complications in obesity [12]. However, the expression of resistin and its epigenetic modification are still in controversy [34][35][36][37][38][39][40][41][42][43][44][45][46]. Kim et al found that, in the DIO rats, the expression levels of different genes in adipose tissue including resistin were upregulated [45], whereas Nowacka-Woszuk reported reduction in the resistin expression in the DIO rats, and no correlation of DNA methylation with transcript levels were observed [46].…”
Section: Discussionsupporting
confidence: 90%
“…Changes in the expression of genes associated with fat metabolism might be resulted from increased expression of adiponectin in the fat, which upon binding to its receptors initiates a series of tissue microenvironment-dependent signal transduction events, including phosphorylation of adenosine monophosphate (AMPK) and increased PPARα ligand activity, and further stimulates fatty acid oxidation in skeletal muscle [36]. Whether the expression of these genes was involved in the resistin expression needs further investigation because the resistin expression in obesity has been in controversy, and in vitro treatment with resistin leads to a reduction in the rate of cellular fatty acid oxidation [37,38]. In addition, we found that the expression of Cidea in the liver was upregulated by the high-fat diet, and antibiotic use reduced its expression, and this might result in less hepatic lipid droplet formation and storage because the highly expressed Cidea in the liver of mice is associated with hepatic steatosis under the high-fat diet feeding [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, resistin, another adipokine, was decreased in the livers of resistant DO mice. Increased resistin levels were previously shown to be associated with reduced fatty acid b-oxidation (He et al, 2018;Ikeda et al, 2013). Lower levels of resistin in resistant DO mice also imply the importance of lipid metabolism in determining the susceptibility to ZILI.…”
Section: Fatty Acid Homeostasismentioning
confidence: 92%
“…Relative to each molecule, fatty acids (such as palmitate) provide three times as much ATP as does glucose. In addition to promoting mitochondrial biogenesis and OXPHOS, PGC‐1α has been shown to drive FAO to maintain energy balance during increased energy demand and help protect mitochondria from the toxic lipid overload . These factors could be beneficial for PGC‐1α’s pro‐neoplastic effects.…”
Section: The Role Of Pgc‐1α In Cancermentioning
confidence: 99%